PENGARUH KONDISI DAN KOSENTRASI BELAJAR DI RUMAH PADA MASA PANDEMI COVID-19 TERHADAP PRESTASI BELAJAR SISWA KELAS X MAN PEMATANGSIANTAR - Rajagukguk, Salome; Nurjana, Pelita (Jurnal Metabio, 2024)
This study aims to determine the Effect of Conditions and Concentration of  Learning at Home During the Covid-19 Pandemic on the Learning Achievement of Class X Students of MAN Pematangsiantar in the 2020/2021 Academic Year. The population in this study was class X which consisted of 4 classes with a total of 160 students. In sampling, 25% of the total population was taken so that the sample could be calculated, namely 160x25% = 40 students, the research instrument used to collect data was a questionnaire filled out by students and DKN (Student Value List), the rest was documentation as additional data. The results of this study are that the influence of conditions and concentration of student learning during the Covid-19 pandemic on the learning achievement of class X students of MAN Pematangsiantar is very influential.